Australian Track & Field Coaches Association
Homepage des Australischen Verbandes der Leichtathletik-Trainer "The Australian Track & Field Coaches Association was founded in 1974 as an association to which all interested in coaching track and field athletics could belong. It is recognised by all Athletics Bodies in Australia as responsible for the coordination and development of athletics coaching. The main objectives of the Australian Track and Field Coaches Association are: To promote coaching in Australia so as to improve the quality of performance and the level of participation in track and field athletics To encourage the accreditation, training and testing of persons to become qualified coaches and to arrange for the proper regulation of such activities To develop the coaching of track and field athletics within clubs, schools, universities, college of education and any other institutions To safeguard the professional integrity and image of ATFCA and its members To represent the interests of coaching and coaches in the decision making processes affecting the ATFCA "